Developing an AI-assisted multimodal critical reading instructional model to enhance problem-solving and metacognitive literacy - Dwipayana, I Kadek Adhi; Sutama, I Made; Rasna, I Wayan; Artika, I Wayan (Edelweiss Applied Science and Technology, 2026)
The low learning outcomes in multimodal critical reading across 12 Study Programs in the Indonesian Language Course constitute a major issue among four universities in Bali. An effort made to address the low level of students’ critical thinking skills was the development of the AI-Assisted Outcome-Based Hypothesis Learning (AI-OBHL) model. This model was designed to enhance students’ critical thinking abilities in analytically, evaluatively, and reflectively understanding multimodal texts. This study employed the Research and Development (R&D) method, with the model design stages referring to the ADDIE framework. The AI-OBHL model comprises six main syntax stages: (1) Determination of Learning Outcomes, (2) Exploration of Problems in the Text, (3) Formulation of Hypothesis, (4) Testing of Hypothesis, (5) Sharing and Response to Arguments, and (6) Reflection of Learning Outcomes. The results of the model’s content and construct validity showed that Aiken’s V values were highly valid. The effectiveness of the OBHL model was demonstrated through a significant improvement in students’ critical reading skills of multimodal text, categorized as a large effect, compared to the control group, which showed only a small to moderate effect. These findings reinforce the urgency of implementing AI-OBHL as a strategic innovation in multimodal-based critical reading learning.